Characterization of non-heme iron aliphatic halogenase WelO5* from Hapalosiphon welwitschii IC-52-3: Identification of a minimal protein sequence motif that confers enzymatic chlorination specificity in the biosynthesis of welwitindolelinones - Zhu, Qin; Liu, Xinyu (Beilstein Journal of Organic Chemistry, 2017)
The in vitro biochemical characterization revealed that iron/2-oxoglutarate (Fe/2OG)-dependent aliphatic halogenase WelO5* in Hapalosiphon welwitschii IC-52-3 has an enhanced substrate specificity towards 12-epi-hapalindole C (1) in comparison to WelO5 in H. welwitschii UTEX B1830. This allowed us to define the origin of the varied chlorinated versus dechlorinated alkaloid structural diversity between the two welwitindolinone producers. Furthermore, this study, along with the recent characterization of the AmbO5 protein, collectively confirmed the presence of a signature sequence motif in the C-terminus of this newly discovered halogenase enzyme family that confers substrate promiscuity and specificity. These observations may guide the rational engineering and evolution of these proteins for biocatalyst application.
Keywords: alkaloid biogenesis; biosynthetic divergency; C–H activation; halogenase; non-heme iron enzyme